PERENCANAAN MANAJEMEN KONSTRUKSI PEMBANGUNAN HOTEL DESA SELUAS KECAMATAN SELUAS KABUPATEN BENGKAYANG: PERENCANAAN MANAJEMEN KONSTRUKSI PEMBANGUNAN HOTEL DESA SELUAS KECAMATAN SELUAS KABUPATEN BENGKAYANG - Aisyah, Nur; Putri, Putri; muhardi, zeldi; widhiyastuti, Rahayu (Jurusan Teknik Sipil Polnep, 2024)
Improving the facilities and infrastructure of the Village Hotel Building in the Se Wide District of Bengkayang Regency is very necessary because the construction of this building will greatly influence the activities in the Village Hotel Building in the Se Wide Subdistrict of Bengkayang Regency. This building planning is very influential because it will produce a building that meets sturdy, economical and aesthetic requirements in order to plan costs, time, quality, human resources and occupational safety and health (K3) requirements. In the management planning for the Hotel Building in the Selebar Village, Selebar Subdistrict, Bengkayang Regency, an analysis of the working drawings used for the management planning object was carried out first. So that job descriptions are obtained from working drawings to plan cost management, time management, quality management, human resource management using direct costs, and occupational health and safety (K3). In writing this final assignment the author used primary data and secondary data. Based on the data that the author has obtained, the final results include a planned cost budget (RAB), amounting to Rp. 15,555,978,000.00, work duration is 184 calendar days, quality management is made using a quality checklist table that is in accordance with standards, human resources (HR) are obtained for foundation reinforcement work. K3 results show that risk control and the need for personal protective equipment are in accordance with standards and needs. Keywords: RAB, time, quality, human resources, K3